2019
DOI: 10.1158/0008-5472.can-19-0181
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Indirect Cell Death Caused by Tumor Vascular Damage after High-Dose Radiotherapy

Abstract: There is increasing evidence that high doses of radiotherapy, like those delivered in stereotactic body radiotherapy (SBRT), trigger indirect mechanisms of cell death. Such effect seems to be two-fold. High doses may trigger an immune response and may cause vascular damage, leading to cell starvation and death. Development of mathematical response models, including indirect death, may help clinicians to design SBRT optimal schedules. Despite increasing experimental literature on indirect tumor cell death cause… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 48 publications
(80 reference statements)
1
16
0
Order By: Relevance
“…In our study, the expression of CD80, CD86 and CCR7 on imDCs was signi cantly increased after co-culture with BT-B cells after hypofractionated radiation. This is consistent with the ndings of Kulzer L et al in colorectal cancer after 5 Gy radiation (Kulzer et al 2014, Rodríguez-Barbeito et al 2019. At the same time, radiation increased the secretion of CCL21 in BC cells, which reached the highest at 10 Gy radiation.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the expression of CD80, CD86 and CCR7 on imDCs was signi cantly increased after co-culture with BT-B cells after hypofractionated radiation. This is consistent with the ndings of Kulzer L et al in colorectal cancer after 5 Gy radiation (Kulzer et al 2014, Rodríguez-Barbeito et al 2019. At the same time, radiation increased the secretion of CCL21 in BC cells, which reached the highest at 10 Gy radiation.…”
Section: Discussionsupporting
confidence: 92%
“…There have been attempts at modelling the contribution of indirect damage [35][36][37], but there is no simple closed-form expression. As suggested in [37], we have investigated ad hoc modifications of the LQ-model with dose-dependent alpha-beta terms of the following form:…”
Section: Radiobiological Modelsmentioning
confidence: 99%
“…There have been attempts at modelling the contribution of indirect damage [35-37] , but there is no simple closed-form expression to model such effect. In order to study whether indirect damage contributes to observed clinical control rates, we hypothesize that an ad hoc modification of the LQ-model with dose-dependent alpha and beta terms, α(d ) and β(d ), may provide better fits to experimental dose-response curves.…”
Section: Methodsmentioning
confidence: 99%
“…For example, if indirect damage is more important for large doses, α(d ) and/or β(d ) should have the form of monotonically-increasing functions. As there is no functional form for the functions α(d ) and β(d ), even though phenomenological forms could be derived from studies like [35-37] , we have investigated simple functional dependencies with the following form:…”
Section: Methodsmentioning
confidence: 99%